Smoothing the adjustment to trade liberalization - Wolfgang Lechthaler; Mariya Mileva (Kiel Institute for the World Economy (IfW), 2014)
We use a dynamic general equilibrium trade model with comparative advantage, heterogeneous firms, heterogeneous workers and endogenous firm entry to analyze economic policy meant to compensate the losers of trade liberalization and reduce the ensuing wage inequality. We consider several instruments of economic policy: a wage tax to redistribute income between skilled and unskilled workers; sector-specific consumption taxes and profit taxes to affect inter-sectoral wage inequality; sector-specific firm entry subsidies, worker sector-migration subsidies and training subsidies to speed up the adjustment process. We find that the re-distributional and efficiency effects of these instruments differ very much. Probably the most potent instrument to reduce the wage inequality after trade liberalization are training subsidies. They increase the supply of skilled workers and thereby reduce the skill premium. The policy also generates inefficiencies because too many workers are trained, but the costs of these inefficiencies are relatively low.
Keywords: E24; F11; F16; J62; 330; trade liberalization; wage inequality; adjustment dynamics; redistribution